(untitled) (Scientific journal of the Fergana State University, 2023)
At the present time, medical pharmacology is developing significantly under the name of microelementology of complex compounds based on amino acids, biogenic organic acids and macro-, microelements. The recent scientific research also provides information on the production of complexes of various amino acids with metal ions and the study of their properties.